Neoliberalismo e saúde: do direito ao negócio - Basile, Ivan Mota (2024)
This research investigates the constitutive and surrounding politicaleconomic relations of Health Social Organization, public-private institutions subsidized by the Executive Branch, the research’s sources are reports and official investigations on São Paulo State’s HSO’s. It aims to comprehend the role of HSO’s as an element of the distributive conflict and the class struggle, investigating their actors, relations and institutional processes, of their creation through their consolidation. Comprehend and describe them as historical objects outcome of political and juridical disputes inside the State for determined constitutional interpretations, for budget control and ideologic hegemony over the States apparatus and civil society